2021 15th European Conference on Antennas and Propagation (EuCAP) 2021
DOI: 10.23919/eucap51087.2021.9410970
|View full text |Cite
|
Sign up to set email alerts
|

Improved Discretization of the Full First-Order Magnetic Field Integral Equation

Abstract: The inaccuracy of the classical magnetic field integral equation (MFIE) is a long-studied problem. We investigate one of the potential approaches to solve the accuracy problem: higher-order discretization schemes. While these are able to offer increased accuracy, we demonstrate that the accuracy problem may still be present. We propose an advanced scheme based on a weak-form discretization of the identity operator which is able to improve the high-frequency MFIE accuracy considerably -without any significant i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In order to be on the safe side regarding the possibly negative influence of ker G ๐œถ LO ,๐œท LO on the one hand and to ensure a sufficient accuracy improvement on the other hand, slightly larger values -๐›พ 0.5 = 0.5, ๐›พ 1.0 = 0.8, and ๐›พ 1.5 = 0.925 -are chosen in the following. The underlying mesh refinement analyses for these proposed values of ๐›พ ๐‘ , ๐‘ โˆˆ {0.5, 1.0}, have been presented in [34].…”
Section: A Choosing a Suitable Weighting Factor For Accurate Mfie Sca...mentioning
confidence: 99%
See 2 more Smart Citations
“…In order to be on the safe side regarding the possibly negative influence of ker G ๐œถ LO ,๐œท LO on the one hand and to ensure a sufficient accuracy improvement on the other hand, slightly larger values -๐›พ 0.5 = 0.5, ๐›พ 1.0 = 0.8, and ๐›พ 1.5 = 0.925 -are chosen in the following. The underlying mesh refinement analyses for these proposed values of ๐›พ ๐‘ , ๐‘ โˆˆ {0.5, 1.0}, have been presented in [34].…”
Section: A Choosing a Suitable Weighting Factor For Accurate Mfie Sca...mentioning
confidence: 99%
“…The approaches with div-conforming basis functions often choose curl-conforming testing functions or a mixture of curl-and div-conforming ones [23]- [26]. Furthermore, it was demonstrated that div-conforming HO expansion approaches may improve the accuracy of both the EFIE and MFIE [27]- [34], where it remains unclear whether the MFIE inaccuracy issues are really completely resolved or only partially. More recently, it was proposed to improve the accuracy of the high-frequency RWG MFIE by applying a weak-form (WF) discretization scheme for the discretized identity operator while working with classical div-conforming RWG testing functions [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approaches with div-conforming basis functions often choose curl-conforming testing functions or a mixture of curl-and div-conforming ones [23]- [26]. Furthermore, it was demonstrated that div-conforming HO expansion approaches may improve the accuracy of both the EFIE and MFIE [27]- [34], where it remains unclear whether the MFIE inaccuracy issues are really completely resolved or only partially. More recently, it was proposed to improve the accuracy of the high-frequency RWG MFIE by applying a weak-form (WF) discretization scheme for the discretized identity operator while working with classical div-conforming RWG testing functions [26].…”
Section: Introductionmentioning
confidence: 99%
“…In particalur, we demonstrate that a hierarchical HO basis [28]- [30] is only capable of curing the MFIE inaccuracies in part and additional measures seem to be required to boost the MFIE accuracy to really good levels. Preliminary results regarding the accurate full first-order discretization of the MFIE only are found in [34].…”
Section: Introductionmentioning
confidence: 99%